Effective police investigative practices: an evidence-assessment of the research. Issue 4 (23rd June 2021) - Prince, Heather; Lum, Cynthia; Koper, Christopher S.
Abstract : Purpose: Detective work is a mainstay of modern law enforcement, but its effectiveness has been much less evaluated than patrol work. To explore what is known about effective investigative practices and to identify evidence gaps, the authors assess the current state of empirical research on investigations. Design/methodology/approach: The authors assess the empirical research about the effectiveness of criminal investigations and detective work in resolving cases and improving clearance rates. Findings: The authors' analysis of the literature produced 80 studies that focus on seven categories of investigations research, which include the impact that case and situational factors, demographic and neighborhood dynamics, organizational policies and practices, investigative effort, technology, patrol officers and community members have on case resolution. The authors' assessment shows that evaluation research examining the effectiveness of various investigative activities is rare. However, the broader empirical literature indicates that a combination of organizational policies, investigative effort and certain technologies can be promising in improving investigative outcomes even in cases deemed less solvable. Research limitations/implications: From an evidence-based perspective, this review emphasizes the need for greater transparency, evaluation and accountability of investigative activities given the resources and importance afforded to criminal investigations. Originality/value: This review is currently the most up-to-date review of the state of the research on what is known about effective investigative practices.